Narasi Realisme Magis dalam Novel Mustika Zakar Celeng Karya Adia Puja - Andriana, Wahyu Dian; Rengganis, Ririe; Sudikan, Setya Yuwana (Edukasi Lingua Sastra, 2024)
This research aims to describe Wendy B Faris' forms of magical realism in the novel Mustika Zakar Celeng by Adia Puja, including 1) irreducible magical elements, 2) phenomenal world, 3) unsettling doubts, 4) incorporation of nature, 5) disruption of space, time, and identity, and 6) magical realism narrative in the novel Mustika Zakar Celeng. The research approach used in this study is a qualitative approach with descriptive method. The data source used, namely the novel Mustika Zakar Celeng by Adia Puja with data in the form of words, phrases, sentences, and paragraphs relevant to the research focus. The data collection techniques used in this research are listening and recording techniques. Meanwhile, the data analysis technique used is hermeneutic technique. Based on the results of the research, it shows that the novel Mustika Zakar Celeng contains five elements of magical realism, including 1) five data of irreducible elements, 2) three data of phenomenal world, 3) two data of unsettling doubts, 4) three data of world merging, and 5) four data of interference with time, space, and identity. The relationship between the five elements can be seen in the characters of Kang Kopral, Tobor, and Ki Ama Hudlan as real characters who interact with the Queen of Siluman Celeng as a magical character. All of these elements are interconnected and continuous, forming a series of magical realism. Kata Kunci: Myth; Wendy B Faris' Narrative of Magical Realism; Mustika Zakar Celeng Novel;